Model OPS sebagai Strategi Efektif Pengelolaan Sampah untuk Meningkatkan Kesejahteraan Psikologis Santri di Pesantren Al Furqon Ponorogo: Pengabdian - Armyati, Eky Ocviana; Sudarno, Sudarno; Rahayu, Yayuk Dwi; Mashudi, Sugeng (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Waste management problems in Islamic boarding schools have been identified as factors that may reduce residential comfort, environmental health, and students’ psychological well-being. This community service program aimed to optimize waste management through the Optimalized Waste Management (OPS) approach, comprising education, source separation, composting, and participatory monitoring. Activities were conducted at Pesantren Al Furqon Ponorogo over 12 weeks and involved 93 students and dormitory managers. Interventions included visual media–based counseling; training on separating organic, inorganic, and residual waste; hands-on simple composting; provision of facilities (segregated bins and composters); and mentoring to establish “green habits.” Evaluation was performed using pre–post knowledge tests, observations of segregation compliance, weighing of waste volumes, and assessments of psychological well-being using the WHO-5 and the short version of WEMWBS. Results showed a 82,7 average increase in knowledge; segregation compliance reached 90%; residual waste volume decreased by 80%; and psychological well-being scores increased by 76 points.